TINGKAT KEMISKINAN PADA RUMAH TANGGA DI KOTA BANJARMASIN - ADINDA FITRIA FEBRIANTY; Khairi Pahlevi (PPJP Universitas Lambung Mangkurat, 2020)
his research aims are, (1) to know poverty potrait based on household poor charateristic in Banjarmasin city, (2) to know relation of poor status with occupation in Banjarmasin city, (3) to know dominant characteristics differentiator poor household and unpoor households in Banjarmasin city.The responden research are 100 households lived in Banjarmasin city. Technical analysis used descriptive statistics and CHAID analysis. The result research show that characteristics of poor households are differents with indicator percentage 22%, the relation between poverty status with occupation status households are strongest and generally the dominant indicator to different poor households with unpoor households are the households can not paying to medicince service on policlinic/hospital, not have saving or goods to sale with minimum value Rp500.000, occupation with salary under Rp600.000 and never/one times week to consumtion milk. Keywords: Poverty Rate, Households Indicator